Design of a dual-polarized microstrip patch antenna with V-shaped slot for 2.4 GHz WLAN applications - Quoc Danh, Luong Vinh; Loi, Vo Ngoc; Kha Duy, Nguyen Tang (Vietnam Journal of Science and Technology, 2014)
This paper presents the design of a dual-polarized microstrip patch antenna used for 2.4 GHz WLAN applications. The designed antenna consists of a circular patch fabricated on low-cost FR-4 substrate with a V-shaped slot carved on its surface and a circular metal reflector. The antenna size and positions of the two feeding ports using coaxial cables are optimized to obtain a dual-polarized antenna having resonant frequency at 2.44 GHz, about 8-dBi peak gain, and the isolation between the two ports below –15 dB in the required band. The measured S-parameter results show good agreement with the simulation. The proposed antenna can be used for 2.4 GHz wireless access points (APs) with 2x2 multiple-input multiple-output (MIMO) antenna systems.